ON LEBESGUE CONSTANTS OF VILENKIN SYSTEMS - Sargsyan, S.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In the paper some properties of Lebesgue constants $\big\{L_n(W)\big\}_{n=1}^{∞}$ of Vilenkin system are investigated. Non almost convergence property for the sequence $\left\{\dfrac{L_n(W)}{\log_2 n}\right\}_{n=2}^{∞}$ is obtained.
Keywords: Vilenkin system, Lebesgue constants, almost convergence